What are the links between maternal social status, hippocampal function, and HPA axis function in children?. Issue 5 (7th August 2013) - Sheridan, Margaret A.; How, Joan; Araujo, Melanie; Schamberg, Michelle A.; Nelson, Charles A.
Abstract: The association of parental social status with multiple health and achievement indicators in adulthood has driven researchers to attempt to identify mechanisms by which social experience in childhood could shift developmental trajectories. Some accounts for observed linkages between parental social status in childhood and health have hypothesized that early stress exposure could result in chronic disruptions in hypothalamic‐pituitary‐adrenal (HPA) axis activation, and that this activation could lead to long‐term changes. A robust literature in adult animals has demonstrated that chronic HPA axis activation leads to changes in hippocampal structure and function. In the current study, consistent with studies in animals, we observe an association between both maternal self‐rated social status and hippocampal activation in children and between maternal self‐rated social status and salivary cortisol in children. Abstract : The association of parental social status with multiple health and achievement indicators in adulthood has driven researchers to attempt to identify mechanisms by which social experience in childhood could shift developmental trajectories. Some accounts for observed linkages between parental social status in childhood and health have hypothesized that early stress exposure could result in chronic disruptions in hypothalamic‐pituitary‐adrenal (HPA) axis activation, and that this activation could lead to long‐term changes. A robust literature in adult animals has demonstrated that chronic HPA axis activation leads to changes in hippocampal structure and function.